(untitled) (Nigerian Journal of Physiological Sciences, 2020)
This study was designed to investigate the source of the glucose released by the small intestine during insulin-induced hypoglycaemia in dogs. Experiments were carried out on fasted, male, anaesthetized mongrel dogs divided into 3 groups (n = 5 each). Group 1 received normal saline (0.2 ml/kg) and served as the control while groups 2-3 were injected with low (5 i.u/kg) and high (8 i.u/kg) doses of insulin. The left femoral artery and vein were cannulated for arterial sampling and intravenous administration route, respectively. Through a midline laparatomy, a vein draining the upper jejunum was cannulated for Intestinal Blood Flow (IBF) measurement and jejunal venous sampling. In stabilized animals, basal measurement of IBF and levels of glucose and lactate in blood were obtained prior to the injections and monitored for 90 minutes post injection. Intestinal Glucose/Lactate Uptake was calculated as the product of IBF and arterio-venous glucose /lactate difference. Jejunal tissue samples were obtained for the determination of Glycogen Content and activities of glycogen synthase, glycogen phosphorylase ‘a’, hexokinase and glucose-6-phosphatase. Data are presented as Mean ± SEM and compared by student’s t-test and ANOVA. Intestinal blood flow was significantly increased by insulin. Within 20 minutes post injection of insulin, glucose uptake was negative while lactate uptake increased. Glycogen content, glycogen synthase activity and hexokinase activity were significantly reduced in the insulin treated groups compared with the control while glycogen phosphorylase ‘a’ and glucose-6-phosphatase activities were increased significantly. In conclusion, the glucose released during insulin-induced hypoglycemia may receive inputs from the breaking down of glycogen and synthesis of glucose within the small intestine.